ANTI-COLONIAL MESSAGES IN AHMAD SANUSI’S TAFSIR MALJA’ AL THALIBIN AND TAMSIYAT AL MUSLIMIN - Lutfi Lutfi (Mimbar Agama Budaya, 2021)
Abstract. This research examines two tafsir works of Ahmad Sanusi Malja’ al thalibin fi tafsiri kalami robbil alamin (in Sundanese) and Tamsiyat al muslimin fi tafsiri kalami Robbil Alamin (Indonesian Bahasa), exploring the messages of anti-colonialism related to justice. This research employs Hermeneutics for the analysis of Sanusi’s messages. This approach provides understanding the social, political, cultural context of the production of the text. This study shows that tafsir has been an inspiration, medium, and tool to shape anti colonial awareness among Sundanese people particularly in Sukabumi region. The resistance is aimed at the Dutch colonial government as well as the religious bureaucrats well known as Pakauman Ulama. Among Sanusi’s criticism that he delivers in his tafsir is about an injustice act done by the colonial government in particular Pakauman Ulama on his isolation as they give support to the exile policy. Historical context of Sanusi’s isolation caused by the conflict between Sanusi and colonial government and the worry of the influence of Sanusi’s ideas of anticolonial sentiment among people. In the literature of tafsir studies so far, it is limited discussion on tafsir material on criticism or as medium of resistance. Abstrak. Penelitian ini mengkaji dua karya tafsir Ahmad Sanusi Malja’ al thalibin fi tafsiri kalami robbil alamin (dalam bahasa Sunda) dan Tamsiyat al muslimin fi tafsiri kalami Robbil Alamin (Bahasa Indonesia), menggali pesan-pesan antikolonialisme yang berkaitan dengan keadilan. Penelitian ini menggunakan Hermeneutika untuk menganalisis pesan-pesan Sanusi. Pendekatan ini memberikan pemahaman konteks sosial, politik, budaya dari produksi teks. Kajian ini menunjukkan bahwa tafsir telah menjadi inspirasi, media, dan alat untuk membentuk kesadaran anti kolonial di kalangan masyarakat Sunda khususnya di wilayah Sukabumi. Perlawanan tersebut ditujukan kepada pemerintah kolonial Belanda serta para birokrat agama yang dikenal dengan sebutan Pakauman Ulama. Di antara kritik Sanusi yang ia sampaikan dalam tafsirnya adalah tentang tindakan ketidakadilan yang dilakukan oleh pemerintah kolonial khususnya Pakauman Ulama atas pengucilannya karena mereka mendukung kebijakan pengasingan. Konteks historis keterasingan Sanusi yang disebabkan oleh konflik antara Sanusi dan pemerintah kolonial dan kekhawatiran pengaruh gagasan Sanusi tentang sentimen antikolonial di kalangan masyarakat. Dalam literatur kajian tafsir selama ini, pembahasan materi tafsir sebatas kritik atau sebagai media perlawanan.